A Study of Successful Students on the Use of Metacognitive Reading Strategies in University of Islam Malang - Izza Rahmatika Mukti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The present study was conducted to investigate deeply the use of metacognitive reading strategies in academic reading by successful students in University of Islam Malang through qualitative approach. Ten invited participants to the interview section are eighth semester students of English Language Education Department, class of 2018, who have high scores on Reading I, II, III, IV courses consistently. The instrument is interview questions adapted from Survey of Reading Strategies (SORS). The results showed that ten successful students utilize various metacognitive strategies in academic reading. In general, support strategies are mostly used by the participants. Further, it is found that there is interconnection among types of metacognitive reading strategies.keywords: Metacognitive strategis, successful Students